Nutrient removal by apple, pear and cherry nursery trees - Sorrenti, Giovambattista; Quartieri, Maurizio; Salvi, Silvia; Toselli, Moreno (Italian Journal of Agronomy, 2017)
Given that nursery is a peculiar environment, the amount of nutrients removed by nursery trees represents a fundamental acquisition to optimise fertilisation strategies, with economic and environmental implications. In this context, we determined nutrient removal by apple, pear and cherry nursery trees at the end of the nursery growing cycle. We randomly removed 5 leafless apple (Golden Delicious/EMLA M9; density of 30,000 trees ha–1), pear (Santa Maria/Adams; density of 30,000 trees ha–1) and cherry (AlexTM/Gisela 6®; density of 40,000 trees ha–1) trees from a commercial nursery. Trees were divided into roots (below the root collar), rootstock (above-ground wood between root collar and grafting point) and variety (1-year-old wood above the grafting point). For each organ we determined biomass, macro- (N, P, K, Ca, Mg, S,) and micro- (Fe, Mn, Zn, Cu, and B) nutrient concentration. Pear trees were the most developed (650 g (dw) tree–1, equal to 1.75 and 2.78 folds than apple and cherry trees, respectively) whereas, independently of the species, variety mostly contributed (>50%) to the total tree biomass, followed by roots and then above-ground rootstock. However, the dry biomass and nutrient amount measured in rootstocks (including roots) represent the cumulative amount of 2 and 3 seasons, for Gisela® 6 (tissue culture) and pome fruit species (generated by mound layering), respectively. Macro and micronutrients were mostly concentrated in roots, followed by variety and rootstock, irrespective of the species. Independently of the tissue, macronutrients concentration hierarchy was N>Ca>K> P>Mg>S. Removed N by whole tree accounted for 6.58, 3.53 and 2.49 g tree–1 for pear, apple and cherry, respectively, corresponding to almost 200, 107 and 100 kg N ha–1, respectively. High amounts of K and Ca were used by pear (130-140 kg ha–1) and apple trees ( 50 and 130 kg ha–1 of K and Ca, respectively), while 25 kg K ha–1 and 55 kg Ca ha–1 were calculated for cherry nursery trees. Among micronutrients, Fe was the most required ( 3 kg ha–1) independently of the species. B removal ranged between 1.2 and 2.4 kg ha–1 (80, 40 and 30 mg tree–1 for pear, apple and cherry, respectively), whereas Mn, Cu and Zn accounted for few hundred g ha–1, irrespective of the species. Given that nutrient concentration among tissues resulted within the same order of magnitude, irrespective of the species, differences in removal were mainly driven by the tree biomass as proved by the significant correlations between plant dry biomass with most of the nutrients we observed.